Role of Transmembrane Protein 16F in the Incorporation of Phosphatidylserine Into Budding Ebola Virus Virions. (5th October 2018) - Younan, Patrick; Iampietro, Mathieu; Santos, Rodrigo I; Ramanathan, Palaniappan; Popov, Vsevolod L; Bukreyev, Alexander
Abstract: Viral apoptotic mimicry, which is defined by exposure of phosphatidylserine (PtdSer) into the outer leaflet of budding enveloped viruses, increases viral tropism, infectivity and promotes immune evasion. Here, we report that the calcium (Ca 2+ )–dependent scramblase, transmembrane protein 16F (TMEM16F), is responsible for the incorporation of PtdSer into virion membranes during Ebola virus infection. Infection of Huh7 cells with Ebola virus resulted in a pronounced increase in plasma membrane-associated PtdSer, which was demonstrated to be dependent on TMEM16F function. Analysis of virions using imaging flow cytometry revealed that short hairpin RNA-mediated down-regulation of TMEM16F function directly reduced virion-associated PtdSer. Taken together, these studies demonstrate that TMEM16F is a central cellular factor in the exposure of PtdSer in the outer leaflet of viral membranes.